2020
DOI: 10.3892/etm.2020.8915
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin affects ox‑LDL‑induced IL‑6, TNF‑α, MCP‑1 secretion and cholesterol efflux in THP‑1 cells by suppressing the TLR4/NF‑κB/miR33a signaling pathway

Abstract: The aim of the present study was to study the molecular mechanism of how curcumin decreases the formation of ox-LDL induced human monocyte macrophage foam cells, promotes the efflux of cholesterol and reduces the secretion of inflammatory cytokines. In vitro cultured THP-1 cells were induced to become macrophages using phorbol-12-myristate-13-acetate. The cells were then pre-treated with curcumin before inducing the foam cell model by addition of oxidized low-density lipoprotein (ox-LDL). Western blot assays w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“…Absence or damage of ABCA1, ABCG1, or SR-BI function can promote the accumulation of foam cells, leading to atherosclerotic lesions and excessive inflammation (30)(31)(32). As previously demonstrated, curcumin can mediate the increase in cholesterol efflux in macrophages by heme oxygenase-1-mediated ABCA1 and SR-BI, while perilla extract and α-asarone can also increase ox-LDL-induced cholesterol efflux in macrophages (25). In the present study, we found that ART increased the ox-LDL-induced expression of ABCA1 and ABCG1 in THP-1-derived macrophages without effect on the SR-BI.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Absence or damage of ABCA1, ABCG1, or SR-BI function can promote the accumulation of foam cells, leading to atherosclerotic lesions and excessive inflammation (30)(31)(32). As previously demonstrated, curcumin can mediate the increase in cholesterol efflux in macrophages by heme oxygenase-1-mediated ABCA1 and SR-BI, while perilla extract and α-asarone can also increase ox-LDL-induced cholesterol efflux in macrophages (25). In the present study, we found that ART increased the ox-LDL-induced expression of ABCA1 and ABCG1 in THP-1-derived macrophages without effect on the SR-BI.…”
Section: Discussionmentioning
confidence: 76%
“…When cholesterol efflux and esterification increase, or cholesterol outflow decreases, macrophages eventually become lipid-rich foam cells. Recent studies have shown that some traditional Chinese medicines and/or their extracts, such as curcumin, purple perilla, tanshinone IIA, and astragalin exhibit an anti-atherosclerotic effect, which is closely related to an increase in cholesterol efflux (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“… 386 PMA is also the standard substance used to differentiate human monocytic leukemia cells into THP-1 macrophages – a standard host system for ABCA transporter evaluation. 231 , 245 , 249 , 256 , 268 , 272 , 275 , 292 , 308 , 310 , 312 - 316 , 321 , 328 , 335 , 338 , 339 , 341 , 342 , 360 , 363 , 364 , 366 , 377 , 384 , 388 - 397 …”
Section: Part I: Status Quomentioning
confidence: 99%
“…Regarding the AMPK pathway ( Figure 3 ), the natural compound curcumin induced ABCA1 / Abca1 mRNA 338 , 388 and ABCA1 protein levels 388 , 394 as well as cholesterol efflux 338 , 388 , 394 in THP-1 338 , 388 , 394 and RAW264.7 394 macrophages, which was also mediated through LXR-α activation. 338 However, these LXR-α activating effects were much more pronounced in combination with the gold standard TO901317.…”
Section: Part I: Status Quomentioning
confidence: 99%
See 1 more Smart Citation